UJI AKTIVITAS ANALGETIK EKSTRAK ETANOL DAUN KELADI TIKUS (Typhonium flagelliiforme Lodd.) PADA MENCIT PUTIH (Mus musculus L.) JANTAN YANG DI INDUKSI ASAM ASETAT 1% - Herdaningsih, Sulastri; Maulana, Iksan; Fauzan, suhaimi (Akademi Farmasi Yarsi Pontianak, 2024)
Pain is an unpleasant sensory and psychological feeling and is associated with tissue damage. With the chemical stimulation method, pain is an unpleasant sensory and emotional feeling associated with tissue damage. This study aims to determine the analgesic activity of ethanol extract of rat taro leaves (Typhonium flagelliforme Lodd.) on male white mice (Mus musculus L.) induced by 1% acetic acid and at what dose of ethanol extract of rat taro leaves (Typhonium flagelliforme Lodd.) has analgesic activity. The percentage results of the ethanol extract of rat taro leaves (Typhonium flagelliforme Lodd.) have analgesic activity which can be seen from the percentage results of Mefenamic Acid of (89.91%) and the ethanol extract of rat taro leaves (Typhonium flagelliforme Lodd.) with a dose of 100 mg/kgBW, 200 mg/kgBB, and 300 mg/kgBB respectively amounted to (52.13%, 60.34 % and 86.58 %). The percentage results of the positive control, extracts 1, 2, and 3 have a significant difference to the negative control of 0.000 (p<0.05). Keywords: Analgesic, ethanol extract of rat taro leaves (Typhonium flagelliforme Lodd.) Male white mice (Mus musculus L.)